2008
DOI: 10.1016/j.bbi.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evidence for a role of the P2X7 receptor in the release of IL-1β in the murine brain

Abstract: The P2X 7 receptor (P2X 7 R) is a purinoceptor expressed predominantly by cells of immune origin, including microglial cells. P2X 7 R has a role in the release of biologically active proinflammatory cytokines such as IL-1β, IL-6 and TNFα. Here we demonstrate that when incubated with lipopolysaccharide (LPS), glial cells cultured from brain of P2X 7 R −/− mice produce less IL-1β compared to glial cells from brains of wild-type mice. This is not the case for TNFα and IL-6. Our results indicate a selective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 63 publications
4
78
0
Order By: Relevance
“…However, it appears that the scenario is more complex as only LPS-induced, but not the basal IL-1b levels are subject to regulation by P2X7 receptors in the rodent brain (Csolle and Sperlagh, 2010;Mingam et al, 2008) and the mood stabilizing phenotype detected in the absence of P2X7 receptors was not transferred with bone marrow transplantation (Csolle et al, 2013b). The contribution of P2X7 receptors present on cells of hematopoietic origin such as peripheral immune cells to behavioral changes detected in naïve animals, therefore, seems minimal.…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 99%
“…However, it appears that the scenario is more complex as only LPS-induced, but not the basal IL-1b levels are subject to regulation by P2X7 receptors in the rodent brain (Csolle and Sperlagh, 2010;Mingam et al, 2008) and the mood stabilizing phenotype detected in the absence of P2X7 receptors was not transferred with bone marrow transplantation (Csolle et al, 2013b). The contribution of P2X7 receptors present on cells of hematopoietic origin such as peripheral immune cells to behavioral changes detected in naïve animals, therefore, seems minimal.…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 99%
“…While P2X7R, in addition to P2X4R and P2X1R, is also expressed by embryonic microglia (Xiang and Burnstock, 2005), its functions remain unknown at these developmental stages. In the adult, P2X7R is involved, in addition to microglia activation and proliferation, in a variety of important effector functions of microglia (Kettenmann et al, 2011), including the release of interleukin (IL)-1␤, IL-1␣, and TNF-␣ (Ferrari et al, 1997;Hide et al, 2000;Brough et al, 2002;Mingam et al, 2008). A remarkable feature of P2X7R is that it promotes the formation of a large pore permeable to hydrophilic moieties up to 900 Da (Surprenant et al, 1996), which has been proposed to evoke IL-1␤ release, to mediate P2X7R effects on the Descartes, France) and by Micaela Galante (IBBMC, CNRS UMR 8619, France).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we compared the inactivation speed of P2X7 receptors in different groups and found that long-term treatment with rotenone not only increased current density, but also extended channel inactivation time. P2X7 receptors play a regulatory role in the secretion of many cytokines [24]. For example, activation of P2X7 receptors in astrocytes inhibits TNF-α secretion [8].…”
Section: Discussionmentioning
confidence: 99%